Enlace entre imagem e palavra: o livro ilustrado criado por mulheres - Munhoz, Estella Maria Bortoncello (My University, 2022)
This dissertation investigates the narrative link between verbal and visual languages in picture books created by women. The research intends to focus on visuality, having as material for analysis the creation of women. The objective is to analyze the articulation between image and word present in the narratives of Brazilian picture books written by women and selected by PNLD Literário of Elementary School (1st to 3rd year) in 2018. The research is justified by the relevance of the picture book in the literary and human formation of children, by the importance of images in the narrative construction of the picture book and by the pertinence of female authorship in children's literature. The dissertation, that has an analytical character, took place through the selection of the books from PNLD Literário written and illustrated by the same author: As cores dos pássaros, by Lúcia Hiratsuka, Dona Nenê e o sumiço do brinco, by Rita Taraborelli and Claro Cleusa. Claro, Clovis, by Raquel Matsushita. Throughout the research, specific objectives guided the work, such as to investigate the path of children's literature and picture books and also the place of the author in this scenario; to describe the educational path of the female authors of the selected books; to analyze the relationship between the image and the word present in picture books produced by women and selected by PNLD Literário 2018 of Elementary School (1st to 3rd year) and to reflect how the image represents elements of the verbal text (like time, space and characters). The theoretical approach focused on literature is based on Bakhtin (2011), Barthes (2011), Coelho (2000), Hunt (2013), Lajolo and Zilberman (2007), Ramos and Panozzo (2011), Zilberman (2003, 2005, 2012) and other authors. For the historical cut of women in society, the research was based on Beauvoir (1970), Dalcastagnè (2007), Duarte (2010), Knapp (2021), Louro (2001), Wollstonecraft (2016), Woolf (2014), Zinani (2014, 2021) and other authors. For the analysis of verbal and visual narrative, the studies of Adam (2008), Dondis (1997), Linden (2018), Heller (2013), Nikolajeva and Scott (2011), Oliveira (2008) and others served as input. For the discussion of the corpus, the paratexts, the construction of the verbal and visual narrative and the relationship between word and image were analyzed in each book. The study demonstrates the relevance of the image, often seen as secondary, in the generation of meanings and in the polysemy of literary books for childhood. Through the research, it was possible to analyze the nuances of each of the selected stories and point out how the approximation and distance between words and images can add meaning to the narratives. The fundamental role of graphic design is also highlighted, which provides the union between the two instances and builds the materiality of the book. Finally, the importance of education for the images is highlighted, since, in the picture book, reading the words is insufficient to understand the possibilities of meaning offered by the narrative.[resumo fornecido pelo autor]
Esta dissertação investiga o enlace narrativo entre as linguagens verbal e visual em livros ilustrados criados por mulheres. Pretende-se, com a pesquisa, enfocar na visualidade tendo como material de análise a criação de mulheres. O objetivo é analisar a articulação entre imagem e palavra presente nas narrativas de livros ilustrados brasileiros elaborados por mulheres e selecionados pelo PNLD Literário de 2018 do Ensino Fundamental (1º a 3º ano). A pesquisa justifica-se pela relevância do livro ilustrado na formação literária e humana das crianças, pela importância das imagens na construção narrativa do livro ilustrado e pela pertinência da autoria feminina na literatura infantil. A pesquisa, de caráter analítico, ocorreu por meio da seleção de obras do PNLD Literário de 2018 escritas e ilustradas pela mesma autora: As cores dos pássaros, de Lúcia Hiratsuka, Dona Nenê e o sumiço do brinco, de Rita Taraborelli e Claro Cleusa. Claro, Clóvis, de Raquel Matsushita. Ao longo da dissertação, objetivos específicos nortearam o trabalho, tais como investigar o percurso da literatura infantil e do livro ilustrado e o lugar da autora nesse cenário; descrever o percurso formativo das autoras das obras selecionadas; analisar a relação entre a imagem e a palavra presente em livros ilustrados produzidos por mulheres e selecionados pelo PNLD Literário 2018 do Ensino Fundamental (1º a 3º ano) e refletir como a imagem representa elementos do texto verbal (tempo, espaço e personagens). A fundamentação teórica voltada à literatura baseia-se em Bakhtin (2011), Barthes (2011), Coelho (2000), Hunt (2013), Lajolo e Zilberman (2007), Ramos e Panozzo (2011), Zilberman (2003, 2005, 2012) e outros autores. Para o recorte histórico da mulher na sociedade, a pesquisa foi embasada em Beauvoir (1970), Dalcastagnè (2007), Duarte (2010), Knapp (2021), Louro (2001), Wollstonecraft (2016), Woolf (2014), Zinani (2014, 2021) e outras autoras. Por fim, na análise da narrativa verbal e visual, os estudos de Adam (2008), Dondis (1997), Linden (2018), Heller (2013), Nikolajeva e Scott (2011), Oliveira (2008) e outros serviram de aporte teórico à pesquisa. Para a discussão do corpus, foi realizado o estudo dos paratextos de cada obra, da construção da narrativa verbal e visual e da relação entre palavra e imagem na condução do enredo. O estudo demonstra a relevância da imagem, muitas vezes tida como secundária, na geração de sentidos e na polissemia das obras literárias para as infâncias. Por meio da pesquisa, foi possível analisar as nuances de cada uma das histórias selecionadas e apontar o quanto a aproximação e o distanciamento entre as palavras e as imagens podem agregar sentidos às narrativas. Destaca-se ainda o papel fundamental do design gráfico, que propicia a união entre as duas instâncias e constrói a materialidade do livro. Por fim, salienta-se a importância de uma educação para as imagens, visto que, no livro ilustrado, ler as palavras é insuficiente para entender as possibilidades de sentido oferecidas pela narrativa. [resumo fornecido pelo autor]
Keywords: Literatura infantil; Livros ilustrados para crianças; Ilustradores - Mulheres; Arte narrativa; Histórias sem palavras; Children's literature; Picture books for children; Illustrators - Women; Narrative art; Stories without words